REVIEW OF ANNAVAHA SROTAS WSR ANNAVAHA SROTAS VIDDH LAKSHANA - Dr. Riva Gupta (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2017)
Srotas are purveyors of the body. It transports different substances present in body. There are various Srotas for different entities. Aacharya described MulaSthan and functions of various Srotas. Beside description of Srotas, AacharyaSushrut also mentioned SrotasViddhLakshana, means symptoms that appear when a Srotas is injured. In modern era there is a need to scrutinize Srotas and SrotasViddhLakshana. Among these Srotas one important Srotas is AnnavahaSrotas as it is related with Anna (food) that is essential for Jeevan so this article is about AnnavahaSrotasand itsViddhLakshan and their approach with modern science. Key words: Srotas, AnnavahaSrotas, MulaSthan, SrotasViddhLakshana